Microgreens: A New Specialty Crop - Danielle Treadwell; Robert Hochmuth; Linda Landrum; Wanda Laughlin (EDIS, 2020)
Microgreens are young, tender greens that are used to enhance the color, texture, or flavor of salads, or to garnish a wide variety of main dishes. Harvested at the first true leaf stage and sold with the stem, cotyledons (seed leaves), and first true leaves attached, they are among a variety of novel salad greens available on the market that are typically distinguished categorically by their size and age. Sprouts, microgreens, and baby greens are simply those greens harvested and consumed in an immature state. This article offers production advice for greenhouse microgreen production. https://edis.ifas.ufl.edu/hs1164